An estimate of women's contribution to agricultural and regional communities in Australia - Jefferson, Therese; Mahendran, Anusha (Inderscience Publishers, 2009)
The invaluable social and economic contribution that women collectively make is often undervalued and underestimated. This paper attempts to redress this to some extent, by providing a contemporary assessment of women's contribution to on farm work in rural and regional communities in Australia. As part of the analysis, women's contributions to on-farm activities, both their paid and unpaid work on farms was examined. Measures of the contribution of women in terms of their paid and unpaid on-farm work were calculated using values derived from specially constructed models. A thorough review of relevant research concerning the determinants of women's contribution to the agricultural sector is also incorporated. The findings presented are thus largely based on current research, with one of the main goals of the exercise being to provide more complete information regarding the contribution of women to agricultural and regional communities, to better assist future policy development.